2015
DOI: 10.1111/jvs.12310
|View full text |Cite
|
Sign up to set email alerts
|

Can leaf area index and biomass be estimated from Braun‐Blanquet cover scores in tropical forests?

Abstract: Questions: The loss and degradation of tropical forests is having severe impacts on the dynamics of understorey plant communities. Understanding these impacts requires efficient ways to measure vegetation change over broad spatial and temporal scales. Leaf area index (LAI) and above-ground biomass are preferred quantitative measures of variation in plant community structure. However, their accurate measurement requires destructive sampling, which can be impractical or inappropriate. Here we test whether semi-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…However, they did not compare estimates with harvested biomass, but only looked at coefficient of variation of the estimates. Our results are in agreement with the findings of Döbert et al (2015), who found that even a semi-quantitative assessment based on Braun-Blanquet scale can provide a reliable proxy for aboveground biomass. Similar to our results, Redjadj et al (2012) also found that visual cover estimation can be accurate in estimating biomass, although they estimated biomass directly (and not cover), and estimation procedure was preceded by a training series.…”
Section: Discussionsupporting
confidence: 93%
“…However, they did not compare estimates with harvested biomass, but only looked at coefficient of variation of the estimates. Our results are in agreement with the findings of Döbert et al (2015), who found that even a semi-quantitative assessment based on Braun-Blanquet scale can provide a reliable proxy for aboveground biomass. Similar to our results, Redjadj et al (2012) also found that visual cover estimation can be accurate in estimating biomass, although they estimated biomass directly (and not cover), and estimation procedure was preceded by a training series.…”
Section: Discussionsupporting
confidence: 93%
“…Disturbed areas, in contrast, promote the growth of a much denser secondary successional vegetation that is characterized by a relatively higher presence of shrubs, herbaceous climbers, and graminoids (Döbert et al . ). Hence, the increased LAI of early‐successional stage native species due to canopy opening is to be expected, unless exotic species became so prevalent in these disturbed areas that even native pioneer species would be excluded.…”
Section: Discussionmentioning
confidence: 97%
“…It was, therefore, estimated from biomass harvesting metrics (see Appendix S1.4 and Döbert et al . ), using a reference measure of specific leaf area (SLA) and the leaf area per unit leaf dry mass (cm 2 /g) for each species (Bréda ). The SLA of fresh leaves (SLA fresh ) has not previously been measured for the majority of tropical rain forest understory species in Borneo.…”
Section: Methodsmentioning
confidence: 99%
“…The allometric relationship can be improved when additional biophysical parameters, such as canopy cover and canopy height, are included in the model (Döbert et al, ; Jensen et al, ; le Maire et al, ; Majasalmi et al, ; Olsoy et al, ). As an alternative, Turner et al () suggested estimating LAI from the sapwood cross‐sectional area, because of their strong physiological relationship.…”
Section: Lai Field Measurementmentioning
confidence: 99%